2015
DOI: 10.5539/ass.v11n24p203
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Mobile Learning Application for Children’s Education: The Development of MFolktales

Abstract: Children learn from what they see and hear. One of the attractive applications is animation story and these children are exposed to various types of animation story. However, not all animation stories presented are suitable for children's education in terms of exaggeration elements applied in animation. Furthermore, the existence of mobile application does not emphasize the touch gesture that is suitable for children's age. Hence, there is a lack of mobile learning applications with education-oriented environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…A study by Tzanakaki et al [ 70 ] reported that succeeding in teaching numeracy to children with ASD requires the use of various models that help students to stay focused. Moreover, children with ASD learn more easily from visual cues and videos promoted to enhance teaching and learning in an inclusive classroom [ 71 , 72 ]. Conoyer et al [ 73 ] evaluated different numeracy domains in the early grades such as oral counting, number recognition, touch count, missing number, and number relations.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Tzanakaki et al [ 70 ] reported that succeeding in teaching numeracy to children with ASD requires the use of various models that help students to stay focused. Moreover, children with ASD learn more easily from visual cues and videos promoted to enhance teaching and learning in an inclusive classroom [ 71 , 72 ]. Conoyer et al [ 73 ] evaluated different numeracy domains in the early grades such as oral counting, number recognition, touch count, missing number, and number relations.…”
Section: Discussionmentioning
confidence: 99%
“…This research used the ADDIE Instructional Design (ID) model consists of five (5) phases which are analysis, design, development, implementation, and evaluation. Since the ADDIE model is known as a generic and traditional process that has historically been used by instructional designers and training developers, especially because of its dynamic and flexible guidelines to build efficient training and performance support tools, it has been determined to be the best option [27][28][29][30]. Besides, the ADDIE ID model was chosen in this research because many researchers used ADDIE in developing educational projects and research [21,27].…”
Section: Methodsmentioning
confidence: 99%
“…Since the ADDIE model is known as a generic and traditional process that has historically been used by instructional designers and training developers, especially because of its dynamic and flexible guidelines to build efficient training and performance support tools, it has been determined to be the best option [27][28][29][30]. Besides, the ADDIE ID model was chosen in this research because many researchers used ADDIE in developing educational projects and research [21,27]. This section discusses the method that had been adapted and the activities involved in developing the MyBrainy Kelate.…”
Section: Methodsmentioning
confidence: 99%
“…Implementasi AR telah banyak dikembangkan untuk pendidikan seperti untuk mempresentasikan kaligrafi secara interaktif [12], untuk pembelajaran kimia obat [13], dan pemodelan visual-haptic untuk sistem pelatihan operasi thoracoscopic [14]. Pada kenyataanya, banyak aplikasi dengan berbagai jenis animasi ini tidak semua cocok untuk pendidikan anak-anak [15]. Pengembangan applikasi yang cocok untuk anak-anak harus memperhatikan karakteristik anak-anak sebagai pengguna [16].…”
Section: Pendahuluanunclassified